2010
DOI: 10.1016/j.healun.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile left ventricular assist device support as a bridge to decision in patients with end-stage heart failure complicated by pulmonary hypertension

Abstract: BACKGROUND Severe pulmonary hypertension (PH) in heart failure (HF) is a risk factor for adverse outcomes after heart transplantation (HTx). Left ventricular assist devices (LVADs) improve pulmonary hemodynamics, but our understanding of the degree of improvement and the effect on outcomes is still evolving. METHODS We reviewed invasive pulmonary hemodynamics from 58 consecutive patients receiving LVAD support as a bridge to HTx from 1996 to 2003. The primary outcome was change in baseline transpulmonary gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 25 publications
0
39
0
1
Order By: Relevance
“…[291][292][293][294][295] Use of echocardiograms in patients with suspected HF improves disease identification and provision of appropriate medical care. 296 Echocardiographic evaluation should address whether LVEF is reduced, LV structure is abnormal, and other structural abnormalities are present that could account for the clinical presentation. This information should be quantified, including numerical estimates of EF measurement, ventricular dimensions, wall thickness, calculations of ventricular volumes, and evaluation of chamber geometry and regional wall motion.…”
Section: October 15 2013mentioning
confidence: 99%
“…[291][292][293][294][295] Use of echocardiograms in patients with suspected HF improves disease identification and provision of appropriate medical care. 296 Echocardiographic evaluation should address whether LVEF is reduced, LV structure is abnormal, and other structural abnormalities are present that could account for the clinical presentation. This information should be quantified, including numerical estimates of EF measurement, ventricular dimensions, wall thickness, calculations of ventricular volumes, and evaluation of chamber geometry and regional wall motion.…”
Section: October 15 2013mentioning
confidence: 99%
“…7 Although useful for tracking relative trends in pulmonary artery systolic pressure, clinical decisions with regard to transplantation candidacy after LVAD implantation and adjunctive pulmonary hypertension therapy are usually based on direct invasive hemodynamic measurements. 33,34 Additional imaging studies are clearly needed to help determine the incremental role of these noninvasive measurements in predicting outcomes in this population.…”
Section: Pulmonary Artery Pressure and Pulmonary Vascular Resistancementioning
confidence: 99%
“…Nearly the entire cohort experienced a significant decrease in pulmonary artery pressure and PVR with an associated improvement in RV function. Although some studies have demonstrated a decrease in PVR after LVAD [7,8,26], the majority of this literature comes from retrospective, single center data that either included patients on pulmonary vasodilator therapy or did not describe whether such therapy was used. There are also data from a prospective study by Tedford et al [9] that indicates some patients with persistent PH after LVAD insertion do not experience a decrease in PVR over time despite LV unloading.…”
Section: Discussionmentioning
confidence: 99%